Study on the Intervention Mechanism of Cryptotanshinone on Human A2780 Ovarian Cancer Cell Line Using GC-MS-Based Cellular Metabolomics - Tong Wang; Shusheng Yin; Juan Gu; Jingjing Li; Mengmeng Zhang; Jinjun Shan; Xiao Wu; Yongming Li (Pharmaceuticals, 2023)
Cryptotanshinone (CT), an active component of the traditional Chinese medicine Salvia miltiorrhiza Bunge, exhibits a wide range of biological and pharmacological activities. Although the anticancer activity of CT is well known, the knowledge of its effect on the regulation of cancer cell metabolism is relatively new. The present study investigated the anticancer mechanism of CT in ovarian cancer with a focus on cancer metabolism. CCK8 assays, apoptosis assays, and cell cycle assays were conducted to reveal the growth-suppressive effect of CT on ovarian cancer A2780 cells. To explore the potential underlying mechanisms of CT, the changes in endogenous metabolites in A2780 cells before and after CT intervention were investigated using the gas chromatography–mass spectrometry (GC-MS) approach. A total of 28 important potential biomarkers underwent significant changes, mainly involving aminoacyl-tRNA biosynthesis, energy metabolism, and other pathways. Changes in the ATP and amino acid contents were verified with in vitro and in vivo experiments. Our results indicate that CT may exert an anti-ovarian cancer effect by inhibiting ATP production, promoting the protein catabolic process, and inhibiting protein synthesis, which may lead to cell cycle arrest and apoptosis.